Juridical Review Of The Legal Force Of Default Claims In Oral Agreements (Study Of Decision Number 30/Pdt.G/2023/Pn.Pal) - Wati, Sulistia; Fajri, Ibrahim; Mustika, Desty Anggie (Universitas Ibn Khaldun Bogor, 2024)
Juridical Review Of The Legal Force Of Default Claims In Oral Agreements (Study Of Decision Number 30/Pdt.G/2023/PN.Pal), Sulistia Wati, NIM: 201103010732. Oral agreement is a phenomenon that often occurs in the daily life of Indonesian society, for example in buying and selling transactions in the market. In small transactions like this, oral agreements are considered to be an easy and efficient choice. The purpose of this study is to determine the extent of the legal force of oral agreements so that they can be used as a basis for judges' consideration in deciding default cases. This research is a normative juridical research that is analytically descriptive. The type of data used is secondary data consisting of primary legal materials and secondary legal materials. The data collection technique used is a literature study, namely by studying a copy of the Palu District Court Decision Number 30/Pdt.G/2023/PN Pal. The decision was regarding a default case between Abdul Rahman as the Plaintiff and Abdul Rahim as the Defendant. Abdul Rahman sued Abdul Rahim on the basis of default against a money lending agreement made orally. In this case the Judge decided that Abdul Rahim was proven to have made a default. The result of this research is that oral agreements have legal force if they can be proven and fulfill the validity of the agreement as stated in Article 1320 of the Civil Code.